2016
DOI: 10.1111/maec.12395
|View full text |Cite
|
Sign up to set email alerts
|

Ecological assessments of the coral reef communities in the Eastern Caribbean and the effects of herbivory in influencing coral juvenile density and algal cover

Abstract: Caribbean reefs have been unevenly surveyed, with many areas lacking baseline data. In this study, the current status of Orbicella reefs, a structurally complex forereef habitat, was quantified in an understudied region, the Eastern Caribbean. During 2011 the same observers surveyed benthic assemblages, coral juvenile density, herbivorous fishes, and invertebrates at 30 Orbicella reefs in four Eastern Caribbean areas: Antigua, Barbados, St Lucia, and St Vincent and the Grenadines (hereafter St Vincent). Not al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…The high number of small bodied Redtail parrotfish species may be contributing to this trend ( Table 2). Our results also revealed increased coral presence and cover with increasing urchin populations and confirmed previous studies demonstrating that higher Diadema densities are associated with coral recovery (Edmunds and Carpenter, 2001;Carpenter and Edmunds, 2006;Myhre and Acevedo-Gutiérrez, 2007) and lower macroalgal cover (Carpenter and Edmunds, 2006;Myhre and Acevedo-Gutiérrez, 2007;Williams et al, 2016;Rodríguez-Barreras et al, 2018) in the Caribbean. This correlation may also be due to positive feedbacks associated with structural complexity and Diadema populations (Lee, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high number of small bodied Redtail parrotfish species may be contributing to this trend ( Table 2). Our results also revealed increased coral presence and cover with increasing urchin populations and confirmed previous studies demonstrating that higher Diadema densities are associated with coral recovery (Edmunds and Carpenter, 2001;Carpenter and Edmunds, 2006;Myhre and Acevedo-Gutiérrez, 2007) and lower macroalgal cover (Carpenter and Edmunds, 2006;Myhre and Acevedo-Gutiérrez, 2007;Williams et al, 2016;Rodríguez-Barreras et al, 2018) in the Caribbean. This correlation may also be due to positive feedbacks associated with structural complexity and Diadema populations (Lee, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that even at low biomass, parrotfish browser species, which feed specifically on macroalgae, have a significant negative correlation with macroalgal cover. Parrotfish biomass in the Mesoamerican Barrier Reef has been increasing slightly in the past few years, and the populations observed here in Akumal are comparable to country and region-wide parrotfish population sizes (Jackson et al, 2014;McField et al, 2018), indicating that recovering populations may be reaching a threshold in which they can exert effective top down control of algal growth (Williams et al, 2016). Even though total parrotfish biomass was not correlated to lower macroalgal cover, fish grazing activity from non-browser species may have other positive benefits such as contributing to increased coral calcification (Suchley and Alvarez-Filip, 2017) or overall reef accretion (Cramer et al, 2017).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Despite occupying only 0.1% of the ocean, coral reefs play a critical role in marine ecology, and in human sustainability, they are invaluable from a variety of perspectives. They are home to more than a quarter of all the species that inhabit the ocean, provide coastal protection, and support more than 10 millions of people living on tropical coasts [1,2]. Economic goods and ecosystem services of coral reefs are worth more than US $20 trillion annually [3].…”
Section: Introductionmentioning
confidence: 99%
“…But the 2005 sea surface warming episode and massive coral reef bleaching event caused an unprecedented coral mortality episode across the northeastern Caribbean region, including P.R., that mostly impacted large reef-building taxa [11][12][13][14]. More than a decade later, there is still no net recovery among many of the impacted coral species, and reef communities have followed a significantly different trajectory resulting in the emergence of novel ecosystems largely dominated by ephemeral coral species [15] and macroalgal growth [16][17][18]. Although such impacts have been well documented, long-term impacts associated to the emergence of novel benthic assemblages on reef functions, values, and benefits still remain largely unknown.…”
Section: The Emergence Of Novel Ecosystemsmentioning
confidence: 99%